IGF Binding Protein-5 Induces Cell Senescence - Sanada, Fumihiro; Taniyama, Yoshiaki; Muratsu, Jun; Otsu, Rei; Shimizu, Hideo; Rakugi, Hiromi; Morishita, Ryuichi (Frontiers in Endocrinology, 2018)
Cellular senescence is the complex process of deterioration that drives the aging of an organism, resulting in the progressive loss of organ function and eventually phenotypic aging. Senescent cells undergo irreversible growth arrest, usually by inducing telomere shortening. Alternatively, senescence may also occur prematurely in response to various stress stimuli, such as oxidative stress, DNA damage or activated oncogenes. Recently, it has been shown that IGF binding protein-5 (IGFBP-5) with the induction of the tumor suppressor p53 is up regulated during cellular senescence. This mechanism mediates IL-6/gp130-induced premature senescence in human fibroblasts, irradiation-induced premature senescence in human endothelial cells, and replicative senescence in human endothelial cells independent of IGF-I and -II. Additionally, a link between IGFBP-5, hyper-coagulation, and inflammation, which occur with age, has been implicated. Thus, IGFBP-5 seems to play decisive roles in controlling cell senescence and cell inflammation. In this review, we describe the accumulating evidence for this role of IGFBP-5 including our new finding.